2017
DOI: 10.1186/s12885-017-3594-9
|View full text |Cite
|
Sign up to set email alerts
|

New use of low-dose aspirin and risk of colorectal cancer by stage at diagnosis: a nested case–control study in UK general practice

Abstract: BackgroundEvidence from clinical trial populations suggests low-dose aspirin reduces the risk of colorectal cancer (CRC). Part of this reduction in risk might be due to protection against metastatic disease.MethodsWe investigated the risk of CRC among new-users of low-dose aspirin (75–300 mg), including risk by stage at diagnosis. Using The Health Improvement Network, we conducted a cohort study with nested case–control analysis. Two cohorts (N = 170,336 each) aged 40–89 years from 2000 to 2009 and free of can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
41
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 30 publications
7
41
0
Order By: Relevance
“…First, the effect appears early over the treatment course, in agreement with a recently published study. 4 Second, our study was performed in a Mediterranean population and its preventive effect on CRC was of similar magnitude to the one observed in other populations with greater cardiovascular comorbidity, 3,4,8 which suggests that such an effect is independent from lifestyle factors. Our results also show that the chemoprotective effect was not maintained in recent or past users, a finding compatible with the interference of low-dose aspirin into the progression of cancer being a reversible effect on discontinuation.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…First, the effect appears early over the treatment course, in agreement with a recently published study. 4 Second, our study was performed in a Mediterranean population and its preventive effect on CRC was of similar magnitude to the one observed in other populations with greater cardiovascular comorbidity, 3,4,8 which suggests that such an effect is independent from lifestyle factors. Our results also show that the chemoprotective effect was not maintained in recent or past users, a finding compatible with the interference of low-dose aspirin into the progression of cancer being a reversible effect on discontinuation.…”
Section: Discussionsupporting
confidence: 67%
“…1,2 A large number of studies have reported a protective effect of low-dose aspirin against CRC. 3,4 Based on this evidence, in 2016, the updated guidelines of the US Preventive Services Task Force (USPSTF) endorsed the use of low-dose aspirin for the prevention of cardiovascular diseases and CRC among adults aged 50 to 59 years who have a 10% or greater 10-year cardiovascular risk and no increased risk of bleeding with a life expectancy of at least 10 years. 5 For adults aged 60 to 69 years with the same clinical characteristics, the USPSTF recommended individualizing the decision to initiate treatment.…”
mentioning
confidence: 99%
“…Data held includes clinical information entered as part of routine patient care, including prescriptions issued and information communicated from secondary care. Full details of our two original studies, including approval of the study protocols, have been published previously [5,12].…”
Section: Data Source and Study Designmentioning
confidence: 99%
“…Low-dose aspirin is well-established in reducing the risk of ischaemic vascular events [1,2] an effect mediated through its irreversible inhibition of cyclooxygenase I (COX-1) in platelets leading to suppression of thromboxane A 2 [3]. There is mounting evidence from both randomized controlled trials (RCTs) and observational studies that low-dose aspirin protects against colorectal cancer (CRC) [4][5][6] an effect possibly also mediated by platelet inhibition, [7,8] and a factor to be considered when evaluating whether the benefits of low-dose aspirin outweigh the risk of major bleeding in specific patient populations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation